Kultura a styl wypowiedzi autobiograficznej – dyskursywność 1 dzienników Zygmunta Mycielskiego i Stefana Kisielewskiego - Biłas-Pleszak, Ewa (Stylistyka, 2019)
Discourse, understood as a category of the cognitive character, was applied in this article to analyse the diaries of two Polish composers and feature writers – Stefan Kisielewski and Zygmunt Mycielski, written in the communist Poland. The purpose of the analysis was to show how this special cultural, social and political context was reflected in their works and how it affected their choices as far as the style and topics were concerned. This paper was also supposed to single out various types of discourses and discursive strategies in the authors’ diaries. A particular attention was paid to the selfawareness of the writers and methods of its expression, either in a direct or oblique way, which often requires an active, almost “archaeological” reading that involves revealing new reserves of meanings from under another layer of words. The performed analysis leads to the conclusion that various types of discourses (anti-totalitarian, chronicle, critical and musical, political, intimate) are present in the discussed works. The above conclusion invites one to ask the following question (which sets a further direction in the research): To what extent is it an individual feature of the authors’ works and to what extent is it a certain element of the style of this period?